Exploring the Baseline: What Michigan Residents Know About Michigan State University Extension - Laura K. Probyn; Murari Suvedi; Réne Pérez Rosenbaum (Journal of Applied Communications, 2005)
Michigan’s Cooperative Extension Service, now called Michigan State University (MSU) Extension, has a long history of serving the state’s residents, especially in agricultural and rural program areas. Today’s Extension works to “help people help themselves” through programs aimed at meeting the needs of urban, suburban, and rural residents. But what do the state’s residents know about the programs offered through this organization? This paper looks at awareness surveys related to Cooperative Extension systems and examines the results of the MSU Extension Market Assessment Survey, a statewide telephone survey conducted by the MSU Institute for Public Policy and Social Research to explore what Michigan residents know about MSU Extension and its main programming areas. Responses were analyzed according to respondents’ ages, education levels, racial and ethnic backgrounds, region of the state and type of community of residence. Analysis showed more than half of Michigan residents were aware of MSU Extension, with wider awareness among older, white and rural residents. However, awareness of MSU Extension programs did not follow this trend. This study will provide information for Extension administrators, educators, and communicators in planning future programming and marketing efforts.